2012
DOI: 10.4244/eijv8i6a115
|View full text |Cite
|
Sign up to set email alerts
|

Vascular healing in drug-eluting stents: differential drug-associated response of limus-eluting stents in a preclinical model of stent implantation

Abstract: Sirolimus and its derivatives have similar effects on endothelial regrowth and neointimal thickening. The observation of greatest fibrin deposition in the experimental EES group indicates that everolimus may affect vascular healing differently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…28,39,40 Interestingly, DES-3 showed no significant differences compared with CS, confirming the safety of this device. Likewise, fibrin deposition around the stents was greater in the DES group, which is an indication of the effect of the drug.…”
Section: Discussionsupporting
confidence: 74%
“…28,39,40 Interestingly, DES-3 showed no significant differences compared with CS, confirming the safety of this device. Likewise, fibrin deposition around the stents was greater in the DES group, which is an indication of the effect of the drug.…”
Section: Discussionsupporting
confidence: 74%
“…Both DES showed increased fibrin deposition when compared to BMS, which is considered a fingerprint of drug elution and retention in tissue and has been reported previously [4,23]. The inflammatory reaction to implanted stents in this experiment deserves attention and discussion.…”
Section: Discussionmentioning
confidence: 95%
“…It has been shown that autonomously sirolimus and its derivatives (everolimus, zotarolimus) have similar effects on vascular response and clinical outcomes [4,5], therefore it has been postulated that the polymer and release kinetics were responsible for the negative tissue effect and clinical outcomes. The early generation SES consisted of non-erodible PEVA/PBMA polymers and thick strut profile stent platform which caused anaphylactic and inflammatory reactions, resulting in impaired vessel healing and ultimately adverse thrombotic events [6].…”
Section: Introductionmentioning
confidence: 99%
“…The Xience V EES is based on a stent platform with very thin stent struts that may minimize aberrations in shear stress that, as observed in prior studies , have been shown to contribute to impaired re‐endothelialization, restenosis and possibly stent thrombosis . An optical coherence tomography (OCT) study has shown more complete stent covered at 9 months after deployment of the Xience V EES compared to SES , while everolimus and sirolimus were shown in an in vivo model to confer similar efficacy with respect to strut coverage at 28 days when the stent platform was controlled, suggesting that the platform may play an important role . Nonetheless, a difference was observed in 2‐year TLR rates in patients who had side‐branch intervention, between those who had ballooning only of the side‐branch, and those whose side‐branches were stented (Fig.…”
Section: Discussionmentioning
confidence: 82%